Provision of Media Booklets on Increase Knowledge of Junior School Children - Nusra, ST. Austa; Sudana, I Made; Raharjo, Bambang Budi (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
The Indonesian government has implemented policies to improve the quality of human resources, namely efforts to improve community nutrition. But the implementation has not been optimal, and there are various problems with eating behavior, clean and healthy living behavior, and disease. A Quasi-experimental design with correlational design. The sampling technique was purposive, proportional, and random sampling with 100 samples. This research took time in June-July 2022. Univariate describes the characteristics of the subject. Bivariate on two variables related or correlated. Based on the Spearman correlation test, the p-value of work (0.634) with a value of (ρ) 0.048, education (0.085) with (ρ) -0.173, infrastructure (0.518) with a value of (ρ) 0.065, school support (0.127) with a value of (ρ) 0.062, parental support (0.010) with (ρ) 0.255 and peer support (0.005) with (ρ) -0.034. Predisposing factors on the variables of work and education through booklet media on knowledge of anemia prevention 0.005. Enabling factors through booklet media on knowledge of anemia prevention were not significantly related to p-value 0.005. The reinforcing factor on the variables of school support and peer support through booklet media on knowledge of anemia prevention, was not significantly related to a p-value of 0.005, but the parental support variable had a significant relationship p-value of 0.005.